1981
DOI: 10.1063/1.92750
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxial growth of single-crystal Fe films on GaAs

Abstract: Molecular beam epitaxy methods have been used to grow good quality magnetic single-crystal films of bcc Fe on fcc GaAs substrates. These films were characterized by Auger, reflection high energy electron diffraction (RHEED) and ferromagnetic resonance (FMR) techniques. Both RHEED and FMR indicate that the best crystal quality occurs for substrate temperatures in the 175–225 °C range. For 200-Å films the Fe surface lattice constant agrees with that of bulk α-Fe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
10

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(77 citation statements)
references
References 3 publications
2
65
0
10
Order By: Relevance
“…With increasing film thickness, the diffraction spots become sharper, i.e., the step density decreases and the film surface becomes flatter as previously observed. 24 For both GaAs orientations, Fe films deposited onto heated-only substrates did not show a diffraction image until the thickness exceeded approximately 15 Å, indicating more disordered growth. For thicker Fe films the LEED spots showed the same features as in the case of films grown on sputter-annealed substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing film thickness, the diffraction spots become sharper, i.e., the step density decreases and the film surface becomes flatter as previously observed. 24 For both GaAs orientations, Fe films deposited onto heated-only substrates did not show a diffraction image until the thickness exceeded approximately 15 Å, indicating more disordered growth. For thicker Fe films the LEED spots showed the same features as in the case of films grown on sputter-annealed substrates.…”
Section: Methodsmentioning
confidence: 99%
“…36 Pseudomorphic Fe films on GaAs are compressed due to a lattice mismatch of 1.36%. The analysis of the separation of RHEED streaks for Fe films deposited onto GaAs͑110͒ suggests that strain is relaxed after 200 Å via dislocations 24 which are on the same length scale as the observed variation of the magnetization and cubic anisotropy. In Fe/GaAs films additional strain can be induced by the As atoms which are found to occupy face centered sites in the bcc Fe lattice.…”
mentioning
confidence: 99%
“…1 Previous work has shown that high-quality epitaxial growth of ͑bcc͒ Fe can be achieved on GaAs͑110͒ and ͑001͒, due in part to the fact that the bcc Fe lattice constant is approximately half that of zinc-blende GaAs (2a Fe /a GaAs ϭ1.013͒. 2,3 Ex situ magnetic measurements of Fe films greater than 25 Å thick grown on oxide-desorbed GaAs͑001͒ substrates have shown that such films often have an in-plane uniaxial component to the magnetic anisotropy, 4 although an ideal bcc Fe͑001͒ film should have fourfold symmetry. There are a number of mechanisms which may contribute to the evolving magnetic anisotropy of the Fe film, including shape anisotropy, epitaxial strain, step anisotropies, or interfacial compound formation, but the source of the uniaxial component remains an open issue.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the Fe/GaAs heterostructure has received the most attention by a significant margin, due in part to the small lattice mismatch (~1.4%) which enables bcc Fe to grow epitaxially upon the zinc-blende crystal structure of GaAs. 3,4 Unfortunately, however, it has been found that the interface of this system deviates somewhat from the 'abrupt' ideal; studies have shown that direct growth of Fe upon GaAs is accompanied by concomitant substrate disruption, resulting in the outdiffusion of As and Ga into the Fe overlayer and the surface segregation of As atoms. 3,[5][6][7][8][9][10][11][12][13] The literature also shows that this dissociation will occur irrespective of reconstruction (be it As-rich or Ga-rich) and growth temperature; these parameters, it seems, influence only the degree of substrate atom incorporation/compound formation observed.…”
Section: Introductionmentioning
confidence: 99%